1999
DOI: 10.1021/ja991098o
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and the Structure of the Transition Aluminas

Abstract: α-Alumina results from the complete dehydration of several minerals of the form Al2O3·nH2O. The “transition” aluminas, γ-alumina, η-alumina, and δ-alumina are known to have a spinel structure but the possibility that they contain hydrogen (H) has been the subject of debate. We present a series of density-functional theory calculations which, together with available experimental data, show that the spinel aluminas exist over a range of hydrogen content captured by the empirical formula H3 m Al2 - m O3, with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
153
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 42 publications
9
153
0
2
Order By: Relevance
“…However, their structures and chemical surface compositions are still not well understood. While the major view is that the γ -alumina has a defect spinel structure, there have been reports that the Al 2 O 3 ·nH 2 O (0 < n <∼ 0.6) form for transition alumina [37]. The α-alumina is the end-structure of transition aluminas formed at high temperature, usually known as "corundum," which exists in nature.…”
Section: Resultsmentioning
confidence: 99%
“…However, their structures and chemical surface compositions are still not well understood. While the major view is that the γ -alumina has a defect spinel structure, there have been reports that the Al 2 O 3 ·nH 2 O (0 < n <∼ 0.6) form for transition alumina [37]. The α-alumina is the end-structure of transition aluminas formed at high temperature, usually known as "corundum," which exists in nature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the formation of γ-alumina was approved by FTIR spectrum (Figure 3). Reference [20] showed that γ-alumina is known to have a spinel structure which exists over a range of hydrogen content captured by the empirical formula H 3m Al 2-m O 3 . According to this result, the IR spectra of Figure 3 obtained in our experiment could be readily explained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has recently been established that there are major disparities in catalyst behavior when different alumina polytypes are used as supports. Among the so-called transition aluminas, all of which are porous and have a cubic spinel structure, [10,11] chromia on g-alumina is a highly active catalyst with a lifetime of several years, whereas the activity of chromia on c-alumina degrades within weeks. [12,13] Differences between the surfaces of these two polytypes are well-known and have been attributed to different reconstructions, controlled by the different distributions of bulk Al vacancies.…”
mentioning
confidence: 99%